ERADICATION STRATEGIES FOR BOMB FISHING PRACTICES IN SALEH BAY - Rafandi, Muhammad Tezar; Junaidi, Muhammad; Gigentika, Soraya (Jurnal Penelitian Perikanan Laut (Albacore), 2025)
Saleh Bay is a water area located in West Nusa Tenggara (NTB) Province, which has experienced significant coral reef ecosystem degradation due to destructive fishing practices using fish bombs. The use of fish bombs has caused severe damage to marine habitats, including a decline in biodiversity and coral reef degradation. This study aims to identify the destructive fishing activities using fish bombs in Saleh Bay and analyze alternative mitigation strategies. Data were collected through interviews, discussions, and field observations in Prajak Subvillage, Batu Bangka Village, Sumbawa Regency. The analysis methods employed were descriptive analysis and SWOT analysis. The results showed that fish bombing activities are still ongoing with 12 active perpetrators. Law enforcement measures, such as the Smart Patrol and penalties for offenders since 2019, have not fully addressed the issue. A total of 70 fish bombing sites were identified around Dangar Island, Liang Island, Lipan Island, and Rakit Island. The proposed alternative strategies in this study include strengthening community-based patrols through local monitoring groups (Pokmaswas), external collaboration for funding, livelihood training for the community, providing incentives for offenders who switch to environmentally friendly fishing methods, and increasing socialization and education regarding applicable regulations. Key words: Fish bombing, law enforcement, patrol, Prajak Subvillage, Saleh Bay